Evaluation of the body weight changes in BALB/c mice after Angiostrongylus cantonensis infection or therapeutic treatment. - Yi-Hao Huang (5983352) (2025)
Mice were assigned to four groups (n = 11/group): Normal (N), Infected (Infect), Infected + albendazole (Infect + Alb), and Infected + albendazole + 3-HBA (Infect + Alb + 3-HBA). Body weight was recorded daily for 21 days. (A) The changes in body weight for N and Infect groups at 0, 7, 14, and 21 days post-infection (dpi). (B) The changes in body weight for Infect, Infect + Alb, and Infect + Alb + 3-HBA groups at 0, 7, 14, and 21 dpi. The data are obtained from independent experiments; ***P < 0.001.